Environmental management activities of NHL teams - Márton, Laura (Applied Studies in Agribusiness and Commerce, 2022)
Over the past two decades, the sports sector has paid increasing and growing attention to understanding sustainability, including the environment, and in particular what can be done in practice. The purpose of this study is to examine the environmental CSR measures adopted by professional hockey teams in North America.To answer my research question, I used a comparative analysis based on secondary data sources. For all 32 teams, I examined the available reports and their information on CSR activities, the information published on the teams' websites, and the research results related to the teams. I have selected 3 teams (Minnesota Wild, Pittsburgh Penguins, Seattle Kraken) that are at the forefront of the issue under study, using an evaluation system based on international literature, and case studies to showcase good practices that can serve as examples for the sports sector.JEL Code: Q56